Analisis Kemampuan Berbicara Anak dalam Penggunaan Bahasa Indonesia dengan Baik dan Benar: Studi Kasus pada Siswa Kelas 3 Sekolah Dasar Negeri Sidoluhur 01 Kecamatan Jaken - Rani Khusnul Fitria; Mei Fita Asri Untari; Iin Purnamasari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study is to describe and explain how the speaking ability of grade 3 elementary school students in Sidoluhur 01 in using Indonesian properly and correctly. The method used in this research is descriptive qualitative. This study uses instruments in the form of interviews, observations, and documentation. The subjects of this study were class teachers and students of grade 3 elementary school students in Sidoluhur 01. The results of the analysis of this study were the level of speaking ability of grade 3 students at elementary school of Sidoluhur 01, included in the medium category, namely 11 students from 13 students were able to have sufficient speaking skills, good for the size in grade 3 elementary school who is undergoing development both psychologically and physically. If it is improved again with regular and directed Indonesian learning, it is very likely that students' speaking skills will increase and fall into the good or even very good category.